Evaluation of the Drug Release Kinetics in Assembled Modular Systems Based on the Dome Matrix Technology - Cid, Alicia Graciela (2020)
Mathematical models are an important tool in pharmaceutical formulationsdevelopment, to evaluate in vitro and in vivo drug release processes and to optimize the design of new systems. Dome Matrix technology allows the combination of modules with different types of drugs, doses, and releases kinetics. This work aimed to design drug release systems based on DomeMatrix technology, with different swelling and erosion properties, to obtain complex drug release profiles and analyze them with simple mathematical models. Most of the release profiles followed a sigmoid curve, with an inflection point corresponding to a change in the release rate behavior. The experimental data were fitted with a simple model recently developed, named the Dual Releasemodel, which consists in the combination of a modified Korsmayer-Peppas model from the beginning to the inflection point and the Lumped model from there until the end. This approach allowed determining relevant pharmaceutical parameters, such as the maximum release rate and the dissolution efficiency, among others. The use of the Dual Release model and the pharmaceutical parameters that characterize the different Dome Matrix modules allows optimizing the choice of the composition and the configuration during the development of a drug delivery system.